PENGARUH STRATEGI THINK TALK WRITE (TTW) DAN MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS NARASI PESERTA DIDIK - Monica Theresia (Jurnal TAROMBO, 2019)
This study aims to examine the influence of Strategy Think Talk Write (TTW) and motivation to learn the skills of narrative writing class V students of SDN 24 Batuang Taba Padang. Using a quasi-experimental design with a 2x2 factorial design. Experimental and control groups were recruited by purposive random sampling. Subjects numbered 49 students in class V year 2016/2017. The test is used to measure the performance of narrative writing skills of learners and questionnaires used to measure the motivation of learners. Data analyzed by t-test and analysis of Varian Two Directions. The results showed that there were significant differences in learning outcomes among students who are taught by a strategy Think Talk Write (TTW) than students taught by conventional approach, and between groups of learners who are highly motivated to learn the high and low. There is no significant interaction between strategy Think Talk Write (TTW) and motivation to learn the skill of writing narrative learners.